An Overview of Ovarian Calyx Fluid Proteins of Toxoneuron nigriceps (Viereck) (Hymenoptera: Braconidae): An Integrated Transcriptomic and Proteomic Approach - Rosanna Salvia; Carmen Scieuzo; Andrea Boschi; Marco Pezzi; Michele Mistri; Cristina Munari; Milvia Chicca; Heiko Vogel; Flora Cozzolino; Vittoria Monaco; Maria Monti; Patrizia Falabella (Biomolecules, 2023)
The larval stages of the tobacco budworm, Heliothis virescens (Fabricius) (Lepidoptera: Noctuidae), are parasitized by the endophagous parasitoid wasp, Toxoneuron nigriceps (Viereck) (Hymenoptera: Braconidae). During the injections of eggs, this parasitoid wasp also injects into the host body the secretion of the venom gland and the calyx fluid, which contains a polydnavirus (T. nigriceps BracoVirus: TnBV) and the Ovarian calyx fluid Proteins (OPs). The effects of the OPs on the host immune system have recently been described. In particular, it has been demonstrated that the OPs cause hemocytes to undergo a number of changes, such as cellular oxidative stress, actin cytoskeleton modifications, vacuolization, and the inhibition of hemocyte encapsulation capacity, which results in both a loss of hemocyte functionality and cell death. In this study, by using a combined transcriptomic and proteomic analysis, the main components of T. nigriceps ovarian calyx fluid proteins were identified and their possible role in the parasitic syndrome was discussed. This study provides useful information to support the analysis of the function of ovarian calyx fluid proteins, to better understand T. nigriceps parasitization success and for a more thorough understanding of the components of ovarian calyx fluid proteins and their potential function in combination with other parasitoid factors.